ATIVIDADE ANTIOXIDANTE E TEORES DE FENÓIS, FLAVONOIDES E TANINOS TOTAIS DE Ocotea velloziana (MEISN.) MEZ. (LAURACEAE) - SILVA, Cristiane Aparecida Rosa Pavera; SILVA, Daniélle Pereira Gregório da; BATISTA-SILVA, Valéria Flávia; SILVA, Ana Francisca Gomes da (ANAIS DO ENIC, 2020)
-